Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M. Blanca Ruiz; Jos, M.; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M Blanca Ruiz; Jos, M; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Nest-site selection and nesting success in the Azure-winged Magpie in Central Spain - Alonso, J A; Muñoz-Pulido, R; Bautista, L M; Alonso, J C (Bird Study, 1991)
Nest-site selection and nesting success in Azure-winged Magpies Cyanopica cyana were studied in 1986 in central Spain. Preferred nest sites were a nonrandom subset of the available habitat. Nests built on evergreen trees had significantly earlier clutch initiation dates than those built on deciduous trees. Birds selected larger trees of each species for nesting, but nests built on very high trees had significantly lower nesting success. Birds tended to locate their nests in a central position relative to the canopy height and as far from the main trunk as possible, without being of the periphery. This may minimize nest accessibility and maximize concealment. Nesting success was higher in the preferred regions of the tree canopy. Predation and inclement weather were probably the factors selecting for the observed patterns in nest-site distribution.
doi: 10.1080/00063659109477066
Keywords: Canopy; Cyanopica cyana; Evergreen and deciduous species (voyant); Nest site selection; Nesting success